Food safety for food security: Relationship between global megatrends and developments in food safety. (October 2017) - King, Thea; Cole, Martin; Farber, Jeffrey M.; Eisenbrand, Gerhard; Zabaras, Dimitrios; Fox, Edward M.; Hill, Jeremy P.
Abstract: Background: There is an urgent need to drive improvements in the efficiency and effectiveness of food chains. The global population is expected to reach at least 9 billion by the year 2050, requiring up to 70% more food, and demanding food production systems and the food chain to become fully sustainable. This challenge is complicated by a number of overarching issues, including increasing complexity of food supply chains, environmental constraints, a growing aging population and changing patterns of consumer choice and food consumption. Within this context, food safety must be an enabler and not inhibitor of global food security. Scope and approach: This paper will highlight how recent developments and trends related to food safety will impact the food sector and ultimately the ability of the sector to deliver food security. Key findings and conclusions: Global megatrends including climate change, a growing and aging population, urbanisation, and increased affluence will create food safety challenges and place new demands on producers, manufacturers, marketers, retailers and regulators. Advances in science and technology such as whole genome sequencing, active packaging, developments in tracing and tracking technologies, information computing technology and big data analysis has the potential to help mitigate the challenges and meet demands, but will also create new challenges. Overcoming a number of these challenges will be difficult for developed economies and large food companies, but even greater for small and medium-sized enterprises (SMEs), developing economies and smallholder farmers, noting that each is a critical component in the global food supply. Highlights: There is an urgent need to drive improvements in the efficiency and effectiveness of food chains. Recent developments and trends related to food safety will impact the food sector and its ability to deliver food security. Food safety must be an enabler and not inhibitor of global food security.